A Bayesian approach for NDT data fusion: The Saint Torcato church case study. (1st February 2015) - Ramos, Luís F.; Miranda, Tiago; Mishra, Mayank; Fernandes, Francisco M.; Manning, Elizabeth
Highlights: Bayesian data fusion applied to ND techniques for historical constructions' assessment. Data fusion at different levels, from subjective and indirect to direct sources of data. A new concept of Trust Factor introduced based on a survey carried out with experts. The method reduces the uncertainties for the structural parameters estimation. Abstract: This paper presents a methodology based on the Bayesian data fusion techniques applied to non-destructive and destructive tests for the structural assessment of historical constructions. The aim of the methodology is to reduce the uncertainties of the parameter estimation. The Young's modulus of granite stones was chosen as an example for the present paper. The methodology considers several levels of uncertainty since the parameters of interest are considered random variables with random moments. A new concept of Trust Factor was introduced to affect the uncertainty related to each test results, translated by their standard deviation, depending on the higher or lower reliability of each test to predict a certain parameter.